Social impact assessment: how do the public help and why do they matter? - Mohamed Osman, Mariana; Abu Bakar, Aisyah; Bachok, Syahriah; Zen, Ismawi (Elsevier, 2015)
In the era of urban regeneration, among many challenges faced by the policy makers is to engage the local community in planning processes. Among many action plans involving the local community is Social Impact Assessment (SIA). The research aimed to underline issues discovered during the profiling phase of the SIA process conducted in Bako Peninsula. The methodology of the research is case study and survey questionnaire. The research discovered issues attributed to social trends and cultural diversity of residents. The findings influenced the next step of the SIA process and forthcoming development of Bako Peninsula.